SELENIUM NANOPARTICLES AND ITS APPLICATION - babu J.D, Monesh; . S, Preetha; Premavathy, Dinesh (International Journal of Psychosocial Rehabilitation, 2020)
Selenium is an important trace element within the diet, required for protection of health and growth; however, its toxicity could cause extreme damage depending on dose and chemical form. Selenium nanoparticles (SeNPs) represent a prospect for nutritional supplementation due to their decreased toxicity and capacity to gradually release selenium after ingestion. Selenium nanoparticles (SeNPs), as a special shape of selenium (Se) supplement, have attracted worldwide attention because of their favorable properties and unique bioactivities. A green and economic way to prepare stable SeNPs has been introduced. Selenium nanoparticles serve to reduce the toxicity and enhance bioactivity. The aim of the present study is to analyse the properties and applications of selenium nanoparticles. Here we have discussed the significance of the selenium nanoparticles and their pharmacological activity. The role of selenium nanoparticles in pharmacological protection against various conditions is presented.